IMPLEMENTASI NILAI -NILAI PANCASILA DALAM PELAKSANAAN PEMILU - Wulandari, Rafih Sri (Bawaslu Provinsi Jawa Barat, 2024)
This study aims to analyze the implementation of Pancasila values in the conduct of elections in Indonesia. As the foundation of the state and the guiding principle of the Indonesian people, Pancasila must serve as the basis for every aspect of election administration. The values contained within Pancasila, such as belief in God, humanitarianism, unity, democracy, and social justice, should be reflected in the democratic process. However, elections often face challenges such as practices that contradict the spirit of Pancasila, including vote-buying, negative campaigning, and election result manipulation. This research uses a qualitative approach with literature review methods and in-depth interviews with political experts and election practitioners. The findings show that while some aspects of elections, such as public participation and general administration, reflect Pancasila values, many challenges remain in realizing elections truly based on justice, unity, and the sovereignty of the people. Therefore, there is a need for stronger supervision, continuous political education, and a more proactive role from election organizers to ensure that elections not only serve as a mechanism for selecting leaders but also reflect the noble values of Pancasila in national life.